2017
DOI: 10.1007/s11356-017-9910-8
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic pollution, a threat to marine ecosystem and human health: a short review

Abstract: Human populations are using oceans as their household dustbins, and microplastic is one of the components which are not only polluting shorelines but also freshwater bodies globally. Microplastics are generally referred to particles with a size lower than 5 mm. These microplastics are tiny plastic granules and used as scrubbers in cosmetics, hand cleansers, air-blasting. These contaminants are omnipresent within almost all marine environments at present. The durability of plastics makes it highly resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
313
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 727 publications
(326 citation statements)
references
References 127 publications
0
313
0
13
Order By: Relevance
“…It is worth noting that, MPs pollution in the terrestrial environment may be more even worse than in the marine environment because of the plastic particles in the industrial production and the use of agricultural plastic film directly . MPs have brought dangers to soil animals and might threaten human health via the food chain or other ways . Study showed that polystyrene nanoparticles were able to damage the intestinal epithelial barrier functions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that, MPs pollution in the terrestrial environment may be more even worse than in the marine environment because of the plastic particles in the industrial production and the use of agricultural plastic film directly . MPs have brought dangers to soil animals and might threaten human health via the food chain or other ways . Study showed that polystyrene nanoparticles were able to damage the intestinal epithelial barrier functions .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 MPs have brought dangers to soil animals and might threaten human health via the food chain or other ways. 2,16 Study showed that polystyrene nanoparticles were able to damage the intestinal epithelial barrier functions. 17 It can be inferred that MPs could potentially injure human intestines, resulting in increased concern in their adverse biological effects.…”
mentioning
confidence: 99%
“…Sharma and Chatterjee (2017) list that introducing strong legislative rules, encouraging long-term monitoring research, increasing public awareness, compelling the use of biodegradable materials, as well as performing the recycling of plastic litters are measurements needed to address the problem at international, national and local levels.…”
Section: Implications For the Recovery Of The Marine Plastics Debrismentioning
confidence: 99%
“…Despite the major impact of plastics debris in marine environments, its recycling remains a little-explored issue (Pietrelli et al 2017), mostly due to difficulties in collecting, separating and characterizing samples for further recovery (Eerkes-Medrano et al 2015;Andrady 2017;Sharma and Chatterjee 2017). Therefore, recent studies have also been investigating this issue with aims to standardize methods for macro-and microplastics extraction in locations such as sediment (Van Cauwenberghe et al 2015;Besley et al 2017), and fresh and seawater (EerkesMedrano et al 2015;Horton et al 2017), as well as characterizing and analyzing their distribution (Graca et al 2017;Mai et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The massive occurrence of microplastics in water can have toxic effects on organisms and cause serious ecological risks [11][12][13]. Toxicity mainly comes from three pathways: (1) pressure of ingestion, such as physical blockages, energy consumption of ingestion; (2) leakage of plastic additives, such as plasticizers; (3) exposure to microplastic-related contaminants [12,14,15].…”
Section: Introductionmentioning
confidence: 99%